Penyimpangan Prinsip Kesantunan Berbahasa dalam ?nteraksi Pembelajaran di Ma Yapira Lapai,Kolaka Utara Sulawesi Tenggara - Baharuddin, Musdalifah; Usman, Usman; Baharman, Baharman (PPJB-SIP (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya)., 2025)
This research aims to describe the types and causes of deviations from the principles of language politeness in learning interactions at Ma Yapira Lapai KolakaÂ UtaraSulawesi Tenggara. This type of research is descriptive qualitative. The data collection techniques used are listening techniques, recording techniques, note-taking techniques and documentation. Researchers carried out data analysis including four stages: data collection, data reduction, data presentation and conclusions. The results of this research found that there were types and causes of deviations from the principles of politeness. There were six types of deviations from the principles of politeness, namely deviations from the maxim of wisdom, deviations from the maxim of generosity, deviations from the maxim of praise, deviations from the maxim of humility, deviations from the maxim of agreement, and deviations from the maxim of sympathy. The causes of deviation from the principles of politeness are that the speaker conveys criticism directly with harsh words, the speaker is driven by emotion when speaking, the speaker is protective of his opinion, the speaker deliberately wants to corner the person he is saying, and the speaker deliberately conveys accusations to the person he is saying. The researchers' suggestions are for students and teachers to pay more attention to the principles of language politeness when speaking in Indonesian language learning interactions and for readers to use this research as a reference in studying language politeness so that they can have the desire to speak politely